Three-Dimensional Displacement after a Medializing Calcaneal Osteotomy in Relation to the Hindfoot Alignment and Osteotomy Angle. Issue 4 (16th October 2019) - Peiffer, Matthias; Belvedere, C.; Clockaerts, S.; Leenders, T.; Barg, Alexej; de Cesar Netto, Cesar; Lintz, Francois; Richter, Martinus; Leardini, A.; Burssens, Arne
Category: Hindfoot Introduction/Purpose: An adult-acquired flatfoot deformity is a three-dimensional (3D) condition characterized by a loss of the medial longitudinal arch, valgus alignment of the hindfoot, and abduction of the midfoot. When conservative measures are not sufficient, a medializing calcaneal osteotomy (MCO) is frequently performed to correct the deformity, but there is lack of data on the associated three-dimensional variables defining the final correction. A possible reason for this shortcoming could be the current image-based analyses, mainly performed on bi-dimensional radiographs. These are hampered by errors in 3D rotations and superimposition of bony structures. The aim of this study was therefore to assess the correlation between the preoperative hindfoot valgus deformity and calcaneal osteotomy angle and the postoperative calcaneal displacement by use of weightbearing CT (WBCT). Methods: Weight-bearing CT scans obtained pre- and post-operatively were analyzed for sixteen patients with a mean age of 49.4 years (range: 18-66 years). Indication for surgery was adult-acquired flat foot deformity stage II. Based on the WBCT images, pre- and post-operative 3D bone morphological models of the tibia, talus, calcaneus, and the second metatarsal were created, on which anatomical bony landmarks were computationally identified to define a Foot Anatomical reference Frame (FAF). This FAF was used to measure valgus deformity pre- and post-operatively, inclination of the osteotomy plane, and displacement of the calcaneus (Fig. 1). Linear regression was conducted to assess the relationship between these measurements. Results: On average, the hindfoot valgus changed from 13.1° (±4.6) preoperatively to 5.7° (±4.3) postoperatively. A mean inferior displacement of 3.2 mm (±1.3) was observed along the osteotomy with a mean inclination angle of 54.6° (±5.6), 80.5° (±10.7), - 13.7° (±15.7) in the axial, sagittal and coronal planes, respectively. A statistically significant positive relationship (P < .05, R2 = 0.6) was found between the preoperative valgus, the axial osteotomy inclination, and the inferior displacement. Conclusion: This study shows that the degree of preoperative valgus of the hindfoot and the axial osteotomy angle are predictive factors for the amount of postoperative plantar displacement of the calcaneus. These findings contrast the general recommendation of performing a 90° calcaneal osteotomy angle, i.e. perpendicular to the lateral calcaneal wall in every patient. The obtained factors should be taken into account when performing a MCO and could be integrated in a computer-based pre- operative planning.